COPD increases the risk of squamous histological subtype in smokers who develop non-small cell lung carcinoma. Issue 8 (28th July 2004) - Papi, A; Casoni, G; Caramori, G; Guzzinati, I; Boschetto, P; Ravenna, F; Calia, N; Petruzzelli, S; Corbetta, L; Cavallesco, G; Forini, E; Saetta, M; et al.
Abstract : Background: Squamous cell carcinoma has a stronger association with tobacco smoking than other non-small cell lung cancers (NSCLC). A study was undertaken to determine whether chronic obstructive pulmonary disease (COPD) is a risk factor for the squamous cell carcinoma histological subtype in smokers with surgically resectable NSCLC. Methods: Using a case-control design, subjects with a surgically confirmed diagnosis of squamous cell carcinoma were enrolled from smokers undergoing lung resection for NSCLC in the District Hospital of Ferrara, Italy. Control subjects were smokers who underwent lung resection for NSCLC in the same hospital and had a surgically confirmed diagnosis of NSCLC of any histological type other than squamous cell. Results: Eighty six cases and 54 controls (mainly adenocarcinoma, n = 50) were enrolled. The presence of COPD was found to increase the risk for the squamous cell histological subtype by more than four times. Conversely, the presence of chronic bronchitis was found to decrease the risk for this histological subtype by more than four times. Among patients with chronic bronchitis (n = 77), those with COPD had a 3.5 times higher risk of having the squamous cell histological subtype. Conclusions: These data suggest that, among smokers with surgically resectable NSCLC, COPD is a risk factor for the squamous cell histological subtype and chronic bronchitis, particularly when not associated with COPD, is a risk factor for the adenocarcinoma histological subtype.